THE PECULIARITIES OF INCLUSIVE EDUCATION PROCESS ORGANIZATION AT HIGHER EDUCATIONAL ESTABLISHMENTS OF THE EUROPEAN UNION COUNTRIES - Давиденко, Г. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The prospects of inclusive education process development at higher educational establishments of the European Union are generalized; basic organizational, methodical and didactic measures and facilities that allow generating a higher return from education of disabled students are reflected. Special focus of the article has been on such major didactic aspects of higher inclusive education as distribution of duties between the participants of inclusive education process; technical and didactical procurement of inclusive education process; specific of entrance examinations, current and midterm examinations of disabled students. It is set up that several measures are taken to generate a higher return from education of students with disabilities in the countries of the European Union such as organization of self-paced course, passing of practices, etc. considering the special necessities of students; implementation of an individual educational plan (free attendance, attendance of basic courses, individual, mixed, distance studies); extension of the term of studies; regularly control plugged of disabled into the process of perception; carrying out of current, module and midterm control in the most optimal form taking into account sensory and functional possibilities of student with disabilities ( tests, verbal questioning, writing questioning, computer diagnostic etc)